2014
DOI: 10.1007/s11356-014-3448-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different nitrogenous nutrients on the cadmium hyperaccumulation efficiency of Rorippa globosa (Turcz.) Thell.

Abstract: This experiment was used to explore whether the 11 nitrogenous nutrients affect the hyperaccumulation of Rorippa globosa (Turcz.) Thell. to Cd. Pot culture experiments using soil spiked with Cd as CdCl2·2.5H2O and 11 nitrogen-containing chemicals were conducted to determine the efficiency of the accumulation of Cd by R. globosa. Application of all 11 nitrogenous nutrients significantly (p < 0.05) enhanced Cd accumulation by R. globosa (Turcz.) Thell. Two major modes of Cd accumulation were observed: (i) throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Concomitantly, the Cd accumulation of those plant parts follows their yields increment as well (Figure 1). This agrees with the findings of [12,[15][16][17][18] who observed greater yields with increased N rates and consequently greater Cd uptake in the studied plants. In fact, N is the most limiting nutrient as far as yield increase is concerned and, in the case of our study, the same evaluations carried out for P and K showed a positive correlation with ryegrass yields but no relationship was found between P and K with Cd accumulation in any plant part (data not shown).…”
Section: Ryegrass Production and Cadmium × Nitrogen Accumulation Relationshipsupporting
confidence: 93%
See 1 more Smart Citation
“…Concomitantly, the Cd accumulation of those plant parts follows their yields increment as well (Figure 1). This agrees with the findings of [12,[15][16][17][18] who observed greater yields with increased N rates and consequently greater Cd uptake in the studied plants. In fact, N is the most limiting nutrient as far as yield increase is concerned and, in the case of our study, the same evaluations carried out for P and K showed a positive correlation with ryegrass yields but no relationship was found between P and K with Cd accumulation in any plant part (data not shown).…”
Section: Ryegrass Production and Cadmium × Nitrogen Accumulation Relationshipsupporting
confidence: 93%
“…Nitrogen is the most important essential nutrient for plants, and N application is the biggest contributor to biomass production [12]. Although some studies suggested that Cd concentration in plants decreased as their biomass increased by N application [13,14], other works concluded that N fertilizer not only improved plants' biomass but also increased their Cd concentration [12,[15][16][17]. In an experiment conducted by Symanowicz et al [18], N fertilization significantly contributed to increase Cd accumulation in the aboveground portion (shoots) of eastern galega.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, abundant freely available mineral N in the soil did not stimulate microbes to produce more NAG, and then resulted in no significant correlation between NAG activity and NH 4 + -N and NO 3 - -N concentrations. As a component part of available N, NH 4 + -N and NO 3 - -N tend to encourage more root growth [ 53 ]. Some studies suggested that root biomass significantly positively correlated with soil respiration [ 21 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, organic matter, nitrogen and extractable P contents were measured using a method described by Lu (Lu, 2000). The pH value was determined by a pH meter (PHS-3B) and the soil to water ratio was 1:2.5 (v/w) (Wei et al, 2015). MDA (malondialdehyde) concentration was determined as described by Zhu et al (Zhu et al, 2019).…”
Section: Sample Determinationmentioning
confidence: 99%